The Urgency of Wills in Preventing Inheritance Disputes from the Perspective of Civil Law and Islamic Law - Yanti Haryanti (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
This study addresses a critical gap in the Indonesian inheritance system, where legal pluralism between the Civil Code and the Compilation of Islamic Law often creates ambiguity in the application of wills, leading to frequent inheritance disputes due to the absence or improper formulation of testamentary documents. The research aims to examine the urgency and legal function of wills as preventive instruments in minimizing inheritance conflicts from both civil and Islamic legal perspectives. This study employs a normative legal research method with statutory and conceptual approaches, relying on primary legal sources, doctrinal analysis, and qualitative interpretation. The findings reveal that a will possesses strong legal authority when it complies with formal and material legal requirements. However, its implementation is constrained by the doctrine of legitime portie in civil law and the one-third limitation in Islamic law, unless agreed otherwise by all heirs. Empirically, the absence of a written and authentic will often triggers disputes due to unclear asset distribution, conflicting interpretations, and weak evidentiary standing. The study emphasizes that wills drafted as notarial deeds provide stronger legal certainty and protection. The global implication of this research lies in offering a model for managing legal pluralism in inheritance systems, highlighting the role of formal legal instruments in dispute prevention, strengthening legal certainty, and promoting equitable wealth distribution across diverse legal traditions.